Desarrollo de indicadores de sostenibilidad ambiental en los páramos de los Illinizas Sur, cantón Latacunga, provincia de Cotopaxi, 2023. - Caguana Achachi, María Anabel (2023)
The objective of this research is to develop environmental sustainability indicators for the conservation of the Cunuyacu hot springs in the Illinizas Sur natural reserve in the San Juan de Pastocalle parish, located in the Latacunga canton, province of Cotopaxi. the generation of environmental sustainability indicators in the Illinizas Sur moors. The methodology used follows a deductive-inductive approach to collect information, based on a bibliographic review. This methodology made it possible to identify the environmental problem and carry out a qualitative analysis with the Atlas.Ti software. To obtain specific data on environmental problems, on-site visits, interviews with the leaders of the parish GAD of San Juan de Pastocalle and surveys of residents and tourists were carried out. In this way, it was possible to obtain precise information about the existing reality, using the PER (Pressure, State, Response) approach to establish environmental indicators. The term "Pressure" refers to activities carried out by human beings that cause changes in the environment. On the other hand, "State" refers to the current condition of the environment and its natural resources. Finally, "Response" refers to the measures and actions implemented by the government or other agencies in response to the identified environmental problems. Establishing a total of 31 environmental sustainability indicators, distributed as follows: 8 indicators for the tourism factor, 6 indicators for the soil factor, 7 indicators for the water factor, 7 indicators for the biodiversity factor and 3 indicators for the management factor. environmental. By implementing preventive and corrective actions based on the selected indicators, current challenges in the Cunuyacu hot springs are addressed through the development of environmental sustainability indicators. This is done with the purpose of promoting a sustainable development approach that is respectful of the ecosystem.